Toxic masculinity men, meaning, and digital media - McGlashan, Mark ca. 20./21. Jh; Mercer, John 1966- (Routledge, Taylor & Francis Group, 2023)
provides an overview of the politics of toxic masculinity and the competing discourses of masculinity that the term brings into view presents a diversity of disciplinary perspectives, critical frameworks and objects of study in the analysis of toxic masculinity draws together essays that ask critical questions about the relations between masculinity, power (and marginality) during a time of cultural and social change
Keywords: Heteronormativität; Geschlechterstereotyp; Neue Medien; Männlichkeit; Frauenfeindlichkeit; Sexualisierte Gewalt; Cultural studies; Gender Studies: Männer und Jungen; Gender studies: men; Kulturwissenschaften; Media studies; Medienwissenschaften; SOCIAL SCIENCE / Gender Studies; Sociology; Soziologie; Aufsatzsammlung